2011
DOI: 10.1089/cbr.2010.0937
|View full text |Cite
|
Sign up to set email alerts
|

Growth Suppression Effects of Recombinant Adenovirus Expressing Human Lactoferrin on Cervical CancerIn VitroandIn Vivo

Abstract: Human lactoferrin (hLF) is a multifunctional glycoprotein that can inhibit cancer growth. The molecular mechanism of hLF-induced tumor growth inhibition is incompletely understood. Moreover, the adenovirus vector-mediated hLF (Ad-hLF) gene therapy on cervical cancer has not been yet characterized. In this study, the replication-deficient Ad-hLF was used to explore tumor growth suppression effects on cervical cancer in vitro and in vivo. The results showed that the recombinant adenovirus encoding hLF delivery r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…It has previously been demonstrated in numerous studies that LTF possesses antitumor action (10,15,21,22). In the current study, it was demonstrated that the mRNA and protein expression levels of LTF in GC were 20-fold lower compared with the adjacent non-cancerous tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been demonstrated in numerous studies that LTF possesses antitumor action (10,15,21,22). In the current study, it was demonstrated that the mRNA and protein expression levels of LTF in GC were 20-fold lower compared with the adjacent non-cancerous tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor suppressor function of LTF has been reported in a variety of tumors (10)(11)(12)(13)(14)(15), however the main functions of LTF are within innate immunity and nutrition (7,8). In a previous study, LTF was observed to inhibit the cell migration of three gastrointestinal cell lines (Caco-2, AGS and IEC-18) in vitro (16).…”
Section: Lactotransferrin Expression Is Downregulated and Affects Thementioning
confidence: 99%
“…Lactoferrin inhibits the proliferation of various types of cells by altering the levels of certain crucial regulators [5], [25], [26]. Ki67, a nuclear antigen expressed during all stages of the cell cycle except G0, is the proliferation marker [27].…”
Section: Resultsmentioning
confidence: 99%
“…Under inflammatory conditions, Lactoferrin knockout mice showed much lower rates of apoptosis compared with rates in WT mice, indicating an increase in necrosis; such an increase may elicit a more intense inflammatory response (Figue 1C). Lactoferrin inhibits proliferation of multiple types of cancer cells, including cervical, gastric, and breast cancer [5], [25], [26]. Deletion of Lactoferrin results in aggravated inflammation and increased secretion of proinflammatory cytokines, which may accelerate the proliferation of colorectal cells, leading to tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Lactoferrin inhibits bacterial growth by sequestering essential iron, and also exhibits non-iron-dependent antibacterial, antifungal, antiviral, antitumor, antiinflammatory, and immunoregulatory activities. Lys/Arg polymorphism (rs1126478) at position 29 in the N-terminal region of human lactoferrin was functionally different, which may contribute to the pathogenesis of localized juvenile periodontitis [28][29][30]. MorenoNavarrete et al assessed the association of circulating lactoferrin concentration and two LTF gene polymorphisms (rs1126477 and rs1126478) with dyslipidemia in men depends on glucose-tolerance status, and found that circulating lactoferrin concentration was inversely associated with fasting triglyceride concentration, body mass index, waist-to-hip ratio, and fasting glucose concentration, and directly correlated with HDL cholesterol concentration.…”
Section: Discussionmentioning
confidence: 99%